On a Zeuthen-type Problem - Jared Ongaro (International Journal of Mathematics And its Applications, 2019)
In this paper, we show that every degree d meromorphic function on a smooth connected projective curve C^2 of degree d>4 is isomorphic to a linear projection from a point pP^2 C to ^1. We then pose a Zeuthen-type problem for calculating the plane Hurwitz numbers.